Seasonal studies of aquatic humic substances from Amazon rivers: characterization and interaction with Cu (II), Fe (II), and Al (III) using EEM-PARAFAC and 2D FTIR correlation analyses - Constantino, Isabela Carreira [UNESP]; Bento, Lucas Raimundo [UNESP]; Santos, Vinicius Sarracini [UNESP]; da Silva, Leila Soares [UNESP]; Tadini, Amanda Maria; Mounier, Stéphane; Piccolo, Alessandro; Spaccini, Riccardo; Cornélio, Marinônio Lopes [UNESP]; Paschoal, Fabiana Maria Monteiro; Junior, Ézio Sargentini; Moreira, Altair Benedito [UNESP]; et al. (Springer Nature, 2024)
Aquatic humic substances (AHS) are defined as an important components of organic matter, being composed as small molecules in a supramolecular structure and can interact with metallic ions, thereby altering the bioavailability of these species. To better understand this behavior, AHS were extracted and characterized from Negro River, located near Manaus city and Carú River, that is situated in Itacoatiara city, an area experiencing increasing anthropogenic actions; both were characterized as blackwater rivers. The AHS were characterized by 13C nuclear magnetic ressonance and thermochemolysis GC–MS to obtain structural characteristics. Interaction studies with Cu (II), Al (III), and Fe (III) were investigated using fluorescence spectroscopy applied to parallel factor analysis (PARAFAC) and two-dimensional correlation spectroscopy with Fourier transform infrared spectroscopy (2D-COS FTIR). The AHS from dry season had more aromatic fractions not derived from lignin and had higher content of alkyls moities from microbial sources and vegetal tissues of autochthonous origin, while AHS isolated in the rainy season showed more metals in its molecular architecture, lignin units, and polysacharide structures. The study showed that AHS composition from rainy season were able to interact with Al (III), Fe (III), and Cu (II). Two fluorescent components were identified as responsible for interaction: C1 (blue-shifted) and C2 (red-shifted). C1 showed higher complexation capacities but with lower complexation stability constants (KML ranged from 0.3 to 7.9 × 105) than C2 (KML ranged from 3.1 to 10.0 × 105). 2D-COS FTIR showed that the COO− and C-O in phenolic were the most important functional groups for interaction with studied metallic ions. Graphical Abstract: (Figure presented.)
Keywords: 13C nuclear magnetic resonance; Amazonian; Aquatic humic substances; Complexation; FTIR two-dimensional correlation spectroscopy